Application of Laplace transforms to solve ODE using MATLAB (Journal of Informatics and Mathematical Sciences, 2015)
Laplace transform is a very powerful mathematical tool applied in various areas of engineering and science. With the increasing complexity of engineering problems, Laplace transforms help in solving complex problems with a very simple approach just like the applications of transfer functions to solve ordinary differential equations. In this paper we present a new technological approach to solve Ordinary differential equation. The application of MATLAB to compute and visualize the Laplace transforms is also discussed.
Keywords: Laplace transforms; Ordinary differential equation (ODE); MATLAB